Titanium Nitride Nanocrystals on Nitrogen‐Doped Graphene as an Efficient Electrocatalyst for Oxygen Reduction Reaction. Issue 44 (17th September 2013) - Liu, Mengjia; Dong, Youzhen; Wu, Yongmin; Feng, Hongbin; Li, Jinghong
<x xml:space="preserve">Abstract</x> Through a facile synthetic process, a TiN/NG hybrid can be prepared as an efficient oxygen reduction reaction electrocatalyst in a four‐electron pathway (see figure). It is low‐cost and widely available and affords strong methanol tolerance and long‐term durability. The synergistic chemical coupling effects between TiN and NG should be responsible for the excellent catalytic activity.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>